Evaluation of the effectiveness of an herbal formulation of Boswellia sacra Flueck. In improving cognitive and behavioral symptoms in patients with cognitive impairment and alzheimer's disease - Mahsa Panahishokouh; Maryam Noroozian; Fatemeh Mohammadian; Mahnaz Khanavi; Mahnaz Mirimoghaddam; Seyed Mehrdad Savar; Maryam Nikoosokhan; Hooshyar Honarmand; Niayesh Mohebbi (Wolters Kluwer Medknow Publications, 2022)
Objective: This study aimed to assess the efficacy of an herbal formulation based on Boswellia sacra in improving cognitive and behavioral symptoms in patients with mild cognitive impairment (MCI) and mild-to-moderate stages of Alzheimer's disease (AD). Methods: A 3-month, parallel-group, placebo-controlled trial was implemented from October 2021 to April 2022. Patients with MCI and mild-to-moderate stages of AD aged above 50 years (n = 60; 40 women, 20 men) enrolled in the study using clinical diagnosis and a score of 10-30 on the mini-mental state examination (MMSE) test. They were assigned into two groups; one receiving a herbal formulation) include B. sacra, Melissa officinalis, Piper longum, Cinnamomum verum, and Physalis alkekengi) three times a day and the other receiving a placebo for 3 months. The main efficacy measures were the changes in cognitive domains based on the MMSE and changes in behavioral and psychiatric symptoms based on neuropsychiatric inventory (NPI) scores compared with baseline. Side effects were also recorded. Findings: Results of this study showed significant differences between the two groups after 3 months in terms of all the assessed variables, including the overall result of the mean score of MMSE and NPI tests (P ≤ 0.001). The herbal formulation had the most considerable effects on the domains of orientation, attention, working memory, delay recall, and language of the MMSE test. Conclusion: Herbal formulation based on B. sacra was significantly effective compared to a placebo in improving cognitive and behavioral symptoms in patients with MCI and mild-to-moderate AD.